Cortical blindness and paraplegia following hypoxic ischemic encephalopathy as a complication of common krait bite - Samanta, SK; Mahapatra, NC; Fariduddin, K; Mazumdar, DB; Mandal, K (Nepalese Journal of Ophthalmology, 2011)
Background: A case report of a successful recovery from paraplegia and cortical blindness following anti-venom injection for a snake bite by a common krait is reported here. Case: A 14-year old male patient was bitten by a common krait. On admission to a tertiary level hospital, he was started with antivenom serum. But the patient developed sudden respiratory distress following anaphylactic shock and he was kept on ventilation. The patient was discharged with paraplegia with loss of vision. He was diagnosed as a case of cortical blindness due to hypoxic ischemic encephalopathy. Subsequently, the patient recovered from paraplegia and regained visual acuity of 6/60 in both eyes (best corrected). The boy was reexamined after four years. Conclusion: Evaluation of victims of neurotoxic snake bite for early signs of respiratory depression and prompt respiratory assistance, even if anti-venom is not available, is most essential as a life saving measure. Key words: snake bite, common krait, anti-venom, hypoxic ischemic encephalopathy, cortical blindness DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5280 Nepal J Ophthalmol 2011; 3(2): 206-209